Efficacy of Vatha Sinthaamani Chooranam and Jeevaratnaathi Kulikai in all Type of Moola Noi (Hemorrhoids) in Traditional Medicine in Srilanka - Nushrath Roshana, M.; Nithiakumar, N. (Global Academic Research Institute Colombo, Sri Lanka, 2022)
Four system of Traditional Medicine have been adopted in Srilanka: Ayurveda, Siddha, Unani and Deshiya Chiktsa. While the different system of Medicines all are coming under the "Srilankan Traditional Medicine". Moola Noi (Hemorrhoid) is also called Mulai Noi, Arippu Noi and Adimulai Noi are swollen veins around the anus. There are four types in modern aspect as well as 21 types in Traditional Medicine. The prevalence of hemorrhoids in the general population is estimated to be 4.4%. Straining during defecation, chronic constipation, eat low fiber food, aging, pregnant, lift heavy weight are the most common causes for Moola Noi. Vaatasinthamani Chooranam and Jeevaratnaathi Kulikai are using to cure the Moola Noi by the traditional Doctor Mrs. M.Pathmanatha, General Specialist in Traditional Medicine in Karaitivu since 1984. Fourty five patients who had this symptom of Moola Noi who attended the Clinics. This study was carried out from 23.08.2017 to 25.11.2017 (3 months). According to the analysis the signs and symptoms in 47% of those used only this Chooranam started gradually disappearing. It was seen reduce the sign and symptoms to 67% of those took only the Kulikai. The signs and symptoms in 87% of those who took this Chooranam and kulikai use started gradually disappearing. The above all three groups observed under the diet restriction. But 3 of the group 2 patients couldn't continue with the treatment as the vathasinthamani chooranam was increased the Moola Noi.
Keywords: Moola noi; Vaathasinthaamani chooranam; Jeevaratna kulikai; Traditional medicine